Politik Organisasi dan Dampaknya terhadap Komitment Organisasi, Kepuasan Kerja, Kinerja dan Organizational Citizenship Behavior (OCB) - Hendra Gunawan; T. Elisabeth Cintya Santosa (Universitas Kristen Maranatha, 2012)
Politic is a life reality in an organization. Political organization is a social reality that must be faced by the member of organization it self where they involve interaction one to another. Some of literatures mention that when the members of one organization have perception that there is a political sense in a organization, that must have a relationship and will give influence to the organization commitment, job satisfaction, job performance, and organizational citizenship behavior (OCB). Furthermore, this study examines relationship and the influence between political organization to organization commitment, job satifcation, job performance and OCB. The result of this research shows that political organization have a relationship to organization commitment and job performance but don’t have relationship to OCB. Political organization also have influence to the organization commitment but don’t have to job performance and OCB. Another result stated that job satisfaction do not fulfill validity test.